2000
DOI: 10.1302/0301-620x.82b5.9561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclic pressure on human monocyte-derived macrophages in vitro

Abstract: Aseptic loosening and osteolysis around prosthetic joints are the principal causes of failure and consequent revision. During this process activated macrophages produce cytokines which are thought to promote osteolysis by osteoclasts. Changes in pressure within the space around implants have been proposed as a cause of loosening and osteolysis. We therefore studied the effect of two different regimes of cyclic pressure on the production of interleukin-1beta (IL-1beta), IL-6 and tumour necrosis factor-alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
1
22
2
1
Order By: Relevance
“…Mechanical factors may also reduce osseointegration in the epiphyseal region. Fluctuations in fluid flow around an implant can induce osteoclastogenesis and contribute to bone resorption 48,49 . The distal part of the implant stem lies within the metaphysis and is not subject to the intraarticular environment, so this part of the stem may be less affected by the intra-articular environment and undergo better osseointegration.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastmentioning
confidence: 99%
“…Mechanical factors may also reduce osseointegration in the epiphyseal region. Fluctuations in fluid flow around an implant can induce osteoclastogenesis and contribute to bone resorption 48,49 . The distal part of the implant stem lies within the metaphysis and is not subject to the intraarticular environment, so this part of the stem may be less affected by the intra-articular environment and undergo better osseointegration.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastmentioning
confidence: 99%
“…Whole blood collected in 3.2% sodium citrate and buffy coat samples were diluted in a ratio of 1:1 with monocyte buffer (phosphate buffered saline [PBS] supplemented with 0.5% bovine serum albumin and 1.5% citrate dextrose phosphate), and the PBMCs were isolated via density gradient centrifugation through Ficoll-Paque Plus (Amersham Pharmacia Biotech, Piscataway, NJ). 22,23 The white cell layer was carefully pipetted from the surface of the separation medium, resuspended in 50 mL monocyte buffer to remove residual medium, and centrifuged at 250g for 10 minutes. The supernatant was removed and this process repeated 2 times.…”
Section: Isolation Of Human Leukocyte Fractionsmentioning
confidence: 99%
“…To put this in context, McEvoy et al (2002) found that primary macrophages could be activated to express pro-osteoclastic genes using cyclic hydrostatic loading only when pressures reached 35,000 Pa. Similarly, Ferrier et al (2000) required cyclic hydrostatic pressures of 138,000 Pa to induce upregulation of interleukin-1β and tumor necrosis-α gene expression in primary human monocytes. It is unlikely that the fluid pressures generated in the MFL system contribute to modulation of osteoclast activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanosensitivity of osteoclastic cells has been demonstrated in vitro using Flexcell, hydrostatic pressure, and fluid flow systems (Ferrier et al, 2000; Guo et al, 2010; Kim et al, 2006; McAllister et al, 2000; McEvoy et al, 2002; Suzuki et al, 2008). Using a parallel plate flow chamber model, McAllister et al found that fluid shear stress (1.6 Pa for 6 h) increased nitric oxide and prostaglandin E 2 production in primary rat pre-osteoclasts (McAllister et al, 2000).…”
Section: Introductionmentioning
confidence: 99%